2020
DOI: 10.1108/bij-03-2019-0114
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between quality and governance mechanisms

Abstract: PurposeRecent literature has highlighted the importance of quality and governance in supply networks. Usually, the relationships between the actors are complex, comprising both formal and informal interactions. Despite recent advances in quality and governance in supply networks, extant literature highlights the lack of quality in healthcare supply-chain networks in relation to governance mechanisms. This paper aims to investigate the role of governance mechanisms and their influence on the quality of healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
6
0
2
Order By: Relevance
“…Martins et al used a multicase approach to study governance mechanisms and their impact on the quality of health care supply networks. For the organizations they studied, they did not find formal network structures and suggested that both formal and informal network structures are needed to avoid quality problems [26]. The design and integration of a well-functioning supply chain constitute important work, but there is also a shortcoming; that is, supply chain research mostly examines organizational cooperation from the perspective of production operations, but it is difficult to include the nonproduction nature of diversified organizations within the scope of research.…”
Section: The Expansion Of Participants In Emergency Managementmentioning
confidence: 99%
“…Martins et al used a multicase approach to study governance mechanisms and their impact on the quality of health care supply networks. For the organizations they studied, they did not find formal network structures and suggested that both formal and informal network structures are needed to avoid quality problems [26]. The design and integration of a well-functioning supply chain constitute important work, but there is also a shortcoming; that is, supply chain research mostly examines organizational cooperation from the perspective of production operations, but it is difficult to include the nonproduction nature of diversified organizations within the scope of research.…”
Section: The Expansion Of Participants In Emergency Managementmentioning
confidence: 99%
“…Based on this premise, this work will use the terms supply chain (SC) and supply network (SN) interchangeably. Studies on supply chain network (SCN) governance have become more prevalent in recent supply chain research (Cardoso de Oliveira et al, 2019;Denolf et al, 2015;Eltantawy, 2016;Formentini and Taticchi, 2016;Gereffi and Lee, 2016;Martins et al, 2020;Soundararajan and Brown, 2016;Varoutsa and Scapens, 2015). These studies emphasize that through its instruments, governance can lead to desired outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to the investigation of supply chain management (SCM), on the one hand, and quality management, on the other hand (Dellana and Kros, 2014;Denolf et al, 2015;Gray and Handley, 2015;Machado et al, 2019;Soltani et al, 2011). Previous research has also shed light on formal and informal instruments' relevance for SC outcomes (Martins et al, 2020;Oliveira et al, 2019). However, research that seeks to investigate the influence of formal and informal instruments, specifically on SN quality, is limited and tangential.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations